2014
DOI: 10.5130/ijcre.v7i1.3394
|View full text |Cite
|
Sign up to set email alerts
|

Using simulation to educate police about mental illness: A collaborative initiative

Abstract: A collaborative initiativefor a three-year period. However, this nurse-led initiative was so successful that the two nursing colleagues were asked to continue to provide educational sessions past the original three-year commitment; the collaboration is now in its sixth year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…This has prompted the utilization of inquests and inquires meant to better understand these exchanges. In 2011 the Mental Health Commission of Canada supported the first large scale Canadian study meant to explore the nature of these interactions (Stanyon et al, 2014). It found that three out of every ten people with MI had come into contact with the police; two out of five people with MI had been arrested; and persons with MI were overrepresented in both lethal and non-lethal interactions involving police weapons (Stanyon et al, 2014).…”
Section: Police As First Respondersmentioning
confidence: 99%
See 4 more Smart Citations
“…This has prompted the utilization of inquests and inquires meant to better understand these exchanges. In 2011 the Mental Health Commission of Canada supported the first large scale Canadian study meant to explore the nature of these interactions (Stanyon et al, 2014). It found that three out of every ten people with MI had come into contact with the police; two out of five people with MI had been arrested; and persons with MI were overrepresented in both lethal and non-lethal interactions involving police weapons (Stanyon et al, 2014).…”
Section: Police As First Respondersmentioning
confidence: 99%
“…In 2011 the Mental Health Commission of Canada supported the first large scale Canadian study meant to explore the nature of these interactions (Stanyon et al, 2014). It found that three out of every ten people with MI had come into contact with the police; two out of five people with MI had been arrested; and persons with MI were overrepresented in both lethal and non-lethal interactions involving police weapons (Stanyon et al, 2014). Similar findings are reported in American literature which indicates that ten percent of police calls involve emotionally disturbed behavior specifically associated with MI (Watson & Fulambarker, 2012).…”
Section: Police As First Respondersmentioning
confidence: 99%
See 3 more Smart Citations